Death masks and professional masks: community, values and ethics in legal education - Paul Maharg (Universitat Politècnica de València, 2014)
This article is a case-study of simulation as a way of learning values and ethics, an approach implemented curriculumwide within a postgraduate, professional legal educational programme, the Diploma in Professional Legal Practice, in Scotland. It involves learning faceto-face using conventional print resources, and also involves online digital resources. While the use of the web to simulate a professional environment is nothing new in itself, the implementation of it (first in the Glasgow Graduate School of Law and then Strathclyde Law School) and on this scale is fairly unique. The article explores the genesis of this approach, its interdisciplinary bases, and its use in various law schools, its effects in building learning communities and facilitating ethical self-revelation.